Biosynthesis of archaeal membrane ether lipids - Jain, Samta (Front Microbiol, 2014)
A vital function of the cell membrane in all living organism is to maintain the membrane permeability barrier and fluidity. The composition of the phospholipid bilayer is distinct in archaea when compared to bacteria and eukarya. In archaea, isoprenoid hydrocarbon side chains are linked via an ether bond to the sn-glycerol-1-phosphate backbone. In bacteria and eukarya on the other hand, fatty acid side chains are linked via an ester bond to the sn-glycerol-3-phosphate backbone. The polar head groups are globally shared in the three domains of life. The unique membrane lipids of archaea have been implicated not only in the survival and adaptation of the organisms to extreme environments but also to form the basis of the membrane composition of the last universal common ancestor (LUCA). In nature, a diverse range of archaeal lipids is found, the most common are the diether (or archaeol) and the tetraether (or caldarchaeol) lipids that form a monolayer. Variations in chain length, cyclization and other modifications lead to diversification of these lipids. The biosynthesis of these lipids is not yet well understood however progress in the last decade has led to a comprehensive understanding of the biosynthesis of archaeol. This review describes the current knowledge of the biosynthetic pathway of archaeal ether lipids; insights on the stability and robustness of archaeal lipid membranes; and evolutionary aspects of the lipid divide and the LUCA. It examines recent advances made in the field of pathway reconstruction in bacteria.